From Recurrent Syncope to Sudden Cardiac Death: Clinical Characteristics in a Chinese Patient Carrying a Plakophilin-2 Gene Mutation - Wenling Liu; Xiaoliang Qiu; Wen Liu; Dayi Hu; Tiangang Zhu; Chunling Wang; Dominik Beer; Li Zhang (Case Reports in Cardiology)
We report a case of Arrhythmogenic Right Ventricular Cardiomyopathy (ARVC) which illustrates the natural progression of disease in the absence of availability of an implanted cardiac defibrillator (ICD). Electrocardiograms and cardiac imaging show the progress of ARVC and these clinical milestones of disease are presented herein.